2016
DOI: 10.3390/ijerph13111062
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a Seasonal Difference-Geographically and Temporally Weighted Regression (SD-GTWR) Model and Comparative Analysis with GWR-Based Models for Hemorrhagic Fever with Renal Syndrome (HFRS) in Hubei Province (China)

Abstract: Hemorrhagic fever with renal syndrome (HFRS) is considered a globally distributed infectious disease which results in many deaths annually in Hubei Province, China. In order to conduct a better analysis and accurately predict HFRS incidence in Hubei Province, a new model named Seasonal Difference-Geographically and Temporally Weighted Regression (SD-GTWR) was constructed. The SD-GTWR model, which integrates the analysis and relationship of seasonal difference, spatial and temporal characteristics of HFRS (HFRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 33 publications
0
25
1
Order By: Relevance
“…Geographically weighted regression (GWR) offers a methodology in which to explore this variation, and this is the approach taken in the present research. GWR has been used to explore a wide range of phenomena, ranging from mosquitos (Ge et al, ; Lin & Wen, ) to obesity (Chalkias et al, ; Wen, Chen, & Tsai, ), participation in higher education (Harris, Singleton, Grose, Brunsdon, & Longley, ), and school attainment (Fotheringham, Charlton, & Brunsdon, ). There have only been a small number of studies where GWR has been used to understand crime.…”
Section: Introductionmentioning
confidence: 99%
“…Geographically weighted regression (GWR) offers a methodology in which to explore this variation, and this is the approach taken in the present research. GWR has been used to explore a wide range of phenomena, ranging from mosquitos (Ge et al, ; Lin & Wen, ) to obesity (Chalkias et al, ; Wen, Chen, & Tsai, ), participation in higher education (Harris, Singleton, Grose, Brunsdon, & Longley, ), and school attainment (Fotheringham, Charlton, & Brunsdon, ). There have only been a small number of studies where GWR has been used to understand crime.…”
Section: Introductionmentioning
confidence: 99%
“…By using ISA [9], GTWR modeling has bandwidth Optimum h = 3947.54. Table 2 shows the estimated estimation of the GTWR model parameters.…”
Section: Results Of Gtwr Modelmentioning
confidence: 99%
“…Where, h is the constant bandwidth performed by the Incremental Spatial Autocorrelation (ISA) method [9]. The Adaptive Gaussian kernel function is used in forming a weighted matrix.…”
Section: Methodsmentioning
confidence: 99%
“…In China, a Kulldorff spatial scan statistic has been used to try and identify the clustering of HFRS, drawing upon data spanning the period 1980 to 2009 [ 17 ]. A Gaussian GWR model has also been used to try and identify the factors influencing HFRS transmission (such as meteorological factors, rodent density, surface mean elevation, water area and human population density) drawing upon data from Hubei that was collected between 2011 and 2015 [ 18 ]. Moran’s I index was adopted for a global spatial autocorrelation analysis that sought to identify the overall spatiotemporal pattern of HFRS outbreaks in Hubei between 2005 and 2014, and Spearman's rank correlation analysis was used at the same time to explore the possible factors influencing the epidemics, such as the weather and the area’s geography [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Research has indicated that HFRS has a characteristic seasonal or cyclic time series-based occurrence [ 42 , 11 ]. In our previous work, a Seasonal Difference—Geographically and Temporally Weighted Regression (SD-GTWR) model was developed as an extension of the GTWR model that sought to use seasonal difference to get stabilized data [ 43 ]. Seasonal difference was used to deal with a non-stationary time series with seasonal distribution characteristics.…”
Section: Introductionmentioning
confidence: 99%